2022
DOI: 10.1093/hr/uhac088
|View full text |Cite
|
Sign up to set email alerts
|

MYB308-mediated transcriptional activation of plasma membrane H+-ATPase 6 promotes iron uptake in citrus

Abstract: Iron-deficiency chlorosis is a common nutritional disorder in crops grown on alkaline or calcareous soils. Although the acclimation mechanism to iron deficiency has been investigated, the genetic regulation of iron acquisition is still unclear. Here, by comparing iron uptake process between an iron-poor-soil-tolerant citrus species Zhique (ZQ) and an iron-poor-soil sensitive citrus species trifoliate orange (TO), we discovered the enhanced root H+ efflux is crucial for the tolerance to iron deficiency in ZQ. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In that sense, the repression of LeHA1 (at 27 and 84 DAT) in leaf tissue under CA treatment and its high expression in root tissue under HLS treatment (at 49 DAT) suggest spatiotemporal expression patterns [14]. Such alterations would imply a modification of H + extrusion from the root tissue into the rhizospheric medium or cellular compartments [17,52]. In addition, humic complexes can induce an acid reaction in the soil by way of their diversity of functional groups [56], affecting LeHA1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, the repression of LeHA1 (at 27 and 84 DAT) in leaf tissue under CA treatment and its high expression in root tissue under HLS treatment (at 49 DAT) suggest spatiotemporal expression patterns [14]. Such alterations would imply a modification of H + extrusion from the root tissue into the rhizospheric medium or cellular compartments [17,52]. In addition, humic complexes can induce an acid reaction in the soil by way of their diversity of functional groups [56], affecting LeHA1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In pea plants (Pisum sativum L.), in addition to higher FRO activity, overexpression of FRO1, IRT1, and HA1 was observed in the roots [15]. Similarly, in cucumber (Cucumis sativus L.) an increase in CsHA1 transcripts was reported in a higher proportion in the roots than in the leaves [16], whereas overexpression of HA6, which allowed for the outflow of H + from the root, was reported in a citrus species [17]. A key regulator in the activation of these mechanisms is FIT, which facilitates Fe uptake [18].…”
Section: Introductionmentioning
confidence: 95%
“…The transcriptional regulation of PM H + ‐ATPase also affects H + secretion ability of apple roots. For example, MYB308 can activate HA6 expression in Zhique, thus promoting root H + efflux and Fe uptake (Fan et al., 2022). MdbHLH104 directly binds to the promoter of MdAHA8 ( MxHA2 ) gene, thus regulating PM H + ‐ATPase activity and H + secretion (Zhao et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Wang et al (2018) also showed in apple that MdMYB58 could modulate Fe homeostasis by directly binding to the MdMATE43 promoter. Fan et al (2022) confirmed that MYB308 could activate HA6 to promote root H + efflux and Fe uptake in Citrus wilsonii , thus dealing with Fe deficiency stress.…”
Section: Myb Tfs Regulate Fe Deficiency Stressmentioning
confidence: 95%